2005
DOI: 10.1111/j.1537-2995.2005.04286.x
|View full text |Cite
|
Sign up to set email alerts
|

Reticulated platelets: a reliable measure to reduce prophylactic platelet transfusions after intensive chemotherapy

Abstract: These encouraging results may allow us to reduce the prophylactic PLT transfusion according to patients RP% increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 35 publications
1
43
0
1
Order By: Relevance
“…This creates the opportunity to defer platelet transfusions that would be given when transfusion decisions are based on platelet counts only. Until present, limited clinical evidence supporting this concept has been reported and there is an evident need for randomized, controlled clinical studies in this field [82,97,98]. A highly interesting observation that also needs to be confirmed is that prophylactic transfusions with high IPF platelet concentrates seem to be more effective than low IPF platelets [99].…”
Section: Clinical Utility Of Reticulated/ Immature Plateletsmentioning
confidence: 99%
“…This creates the opportunity to defer platelet transfusions that would be given when transfusion decisions are based on platelet counts only. Until present, limited clinical evidence supporting this concept has been reported and there is an evident need for randomized, controlled clinical studies in this field [82,97,98]. A highly interesting observation that also needs to be confirmed is that prophylactic transfusions with high IPF platelet concentrates seem to be more effective than low IPF platelets [99].…”
Section: Clinical Utility Of Reticulated/ Immature Plateletsmentioning
confidence: 99%
“…Although an arbitrary cut point (a marker set to include 1% of the negative population), this was similar to other studies with this and other RP staining reagents. Previous studies have used cut points of 0.1%, 0.5%, 1%, and 5% (2,3,5,6,17,22) or even red cell autofluorescence (11) to determine the level at which RP begin. Small changes in the marker position (for example a gain of 0.1%) can have a large impact on the RP value, for these reasons strict adherence to the protocol is needed for this assay.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies showed RP were readily stained with nucleic acid dyes such as Thiazole Orange (TO) (2)(3)(4) and that RP have obvious potential as a sensitive early predictor of bone marrow engraftment (5,6). However difficulties with consistency of analysis have hampered wide-spread adoption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assay is suitable to predict the time of platelet recovery and to optimise platelet transfusion decisions. In fact, reticulated platelets have been successfully employed to manage the platelet transfusion requirement during chemotherapy [23]. In addition, circulating reticulated platelets serve as prognostic markers in ischaemic vascular disease [24].…”
Section: Estimation Of Platelet Turnovermentioning
confidence: 99%